Does intermittent exposure to high altitude increase the risk of cardiovascular disease in workers? A systematic narrative review. Issue 11 (20th November 2020) - Aragón-Vela, Jerónimo; Bejder, Jacob; R Huertas, Jesús; Plaza-Diaz, Julio; Nordsborg, Nikolai B
Abstract : Objective: Several working groups (eg, miners, flight crews and soldiers) are subjected to chronic intermittent hypoxic exposure. The cardiovascular implications have been studied but not systematically reviewed with focus on possible negative health implications. The aim of the present review was to systematically evaluate the hypothesis that intermittent hypoxic exposure causes cardiovascular stress detrimental to health in workers. Design: Systematic review. Data sources: Electronic database search of PubMed, Scopus and Web of Science up to April 2020. Eligibility criteria: Studies of workers ≥18 years repeatedly subjected to months to years of irregular intermittent hypoxia, lasting from a few hours (eg, flight crews), one or a few days (eg, soldiers), or several days to weeks (eg, miners working at high altitude), written in English and evaluating the effect of intermittent hypoxia on cardiovascular disease were included. Animal studies, books, book chapters, personal communication and abstracts were excluded. The primary outcome measure was changes in standardised mortality ratio. Data extraction and synthesis: Two independent reviewers extracted data and assessed risk of bias using the Cochrane Collaboration's tool. Results: 119 articles were identified initially, 31 of which met the inclusion criteria. Of these, 17 were retrospective cohort mortality studies (irregular short-term intermittent hypoxia), and 14 studies were observational (long-term intermittent hypoxia). The population of irregular short-term intermittent hypoxia users (flight crew) showed a lower mortality by cardiovascular disease. Long-term intermittent hypoxia over several years such as in miners or soldiers may produce increased levels of cardiac disorders (12 studies), though this is probably confounded by factors such as obesity and socioeconomic status. Conclusion: This systematic narrative review found that cardiovascular disease mortality in flight crews is lower than average, whereas miners and soldiers exposed to intermittent hypoxia experience increased risks of cardiovascular diseases. The impact of socioeconomic status and lifestyle appears of importance. PROSPERO registry number: CRD42020171301.